'Even now it makes me angry': health care students' professionalism dilemma narratives. Issue 5 (May 2014) - Monrouxe, Lynn V; Rees, Charlotte E; Endacott, Ruth; Ternan, Edwina
<x xml:space="preserve">Abstract</x> Context Medical students encounter situations during workplace learning in which they witness or participate in something unprofessional (so‐called professionalism dilemmas), sometimes having a negative emotional impact on them. Less is known about other health care students' experiences of professionalism dilemmas and the resulting emotional impact. Objectives To examine dental, nursing, pharmacy and physiotherapy students' narratives of professionalism dilemmas: the types of events they encounter ('whats') and the ways in which they narrate those events ('hows'). Methods A qualitative cross‐sectional study. Sixty‐nine health care students (29 dentistry, 13 nursing, 12 pharmacy, 15 physiotherapy) participated in group/individual narrative interviews. Data were analysed using framework analysis (examining the 'whats'), linguistic inquiry and word count software (examining the 'hows' by dilemma type and student group) and narrative analysis (bringing together 'whats' and 'hows'). Results In total, 226 personal incident narratives (104 dental, 34 nursing, 39 pharmacy and 49 physiotherapy) were coded. Framework analysis identified nine themes, including 'Theme 2: professionalism dilemmas', comprising five sub‐themes: 'student abuse', 'patient safety and dignity breaches by health care professionals', 'patient safety and dignity breaches by students', 'whistleblowing and challenging' and 'consent'. Using Linguistic Inquiry and Word Count (liwc) software, significant differences in negative emotion talk were found across student groups and dilemma types (e.g. more anger talk when narrating patient safety and dignity breaches by health care professionals than similar breaches by students). The narrative analysis illustrates how events are constructed and the emotional implications of assigning blame (an ethical dimension) resulting in emotional residue. Conclusion Professionalism dilemmas experienced by health care students, including issues concerning whistleblowing and challenging, have implications for interprofessional learning. By focusing on common professionalism issues at a conceptual level, health care students can share experiences through narratives. The role‐playing of idealised actions (how students wish they had acted) can facilitate synergy between personal moral values and moral action enabling students to commit and re‐commit to professionalism values together.